ASSESSING PSYCHOMETRIC PROPERTIES OF THE SERBIAN VERSION OF THE METACOGNITIVE AWARENESS INVENTORY (MAI) - Bukumirić, Zoran; Stanisavljević, Dejana; Milić, Nataša; Ćirković, Anđa; Milin-Lazović, Jelena; Savić, Marko; Rajović, Nina; Ćorac, Aleksandar; Jović, Jelena; Ilić, Aleksandra; Pajčin, Mirjana; Mugoša, Snežana; et al. (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Metacognition, which refers to the ability to monitor and regulate one’s cognitive processes, plays a crucial role in medical education. Evaluating metacognitive awareness is particularly important for university students, as it impacts their learning strategies and academic performance. The study aimed to examine the psychometric characteristics of the Serbian adaptation of the Metacognitive Awareness Inventory (MAI), emphasizing its construct validity and internal consistency.Materials and methods: This cross-sectional study was conducted with third-year medical students of the University of Belgrade Faculty of Medicine, in October 2024.  The psychometric properties of the Serbian version of the MAI were evaluated by assessing its factorial structure and internal consistency. The MAI consists of 52 items, comprising two primary components: ‘Knowledge of Cognition’ and ‘Regulation of Cognition’. The subcomponents of the ‘Knowledge of Cognition" component were declarative knowledge, procedural knowledge, and conditional knowledge, whereas the subcomponents of the ‘Regulation of Cognition’ component were: planning, information management strategies, comprehension monitoring, debugging strategies, and evaluation.Results: A total of 426 medical students were included in the study. The mean age of the respondents was 21.3±1.4 years, and the majority were females (68.5%). The mean score on the scale was 199.0. The internal consistency analysis of the Serbian version of the MAI questionnaire yielded a Cronbach’s α of 0.94, and a McDonald's ω of 0.95 for the entire scale, which indicates excellent scale reliability. The Serbian version of the MAI questionnaire was validated using confirmatory factor analysis, supporting both the hypothesized eight-factor and two-factor structures. The eight-factor model showed good fit indices (IFI = 0.908, CFI = 0.905, RMSEA = 0.042), with statistically significant factor loadings (p < 0.05). Similarly, the two-factor model demonstrated an adequate fit (IFI = 0.921, CFI = 0.918, RMSEA = 0.039), with all loadings also being significant (p < 0.05).Conclusion: The present study revealed that the Serbian version of the MAI is a reliable and valid tool for assesment medical students’ metacognitive awareness.
Keywords: metacognition; awareness; psychometric properties; internal consistency; construct validity